The Effect of Profitability, Leverage and Company Size on Financial Distress with Institutional Ownership as a Moderating Variable in Restaurant, Hotel and Tourism Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2020 Period - Ranti Nurdiansari (Westscience Press, 2023)
Financial distressis where the condition of financial performance is not healthy. Therefore it is important for companies to know the causes of financial distress. This study aims to determine the effect of profitability, leverage, and firm size on financial distress and also adds institutional ownership as a moderating variable. The population in this study were 34 companies with samples taken of 16 companies in the restaurant, hotel and tourism sector which were listed on the Indonesia Stock Exchange in 2016-2020. This sample was taken using a purposive sampling technique. Methods of data analysis using, descriptive analysis, classic assumption test, multiple linear regression test and also hypothesis testing. The results of this study indicate that profitability has a significant effect on financial distress with a sig value of 0.00 <0.05, leverage has a significant effect on financial distress indicated by a sig value of 0.037 <0.05, and company size does not have a significant effect on financial distress indicated by a value sig 0.476>0.05. while institutional ownership can moderate the relationship between profitability and financial distress indicated by a sig value of 0.000 <0.05, institutional ownership cannot moderate the relationship between leverage and financial distress indicated by a sig value of 0.278> 0.05, and institutional ownership cannot moderate the relationship.